2012
DOI: 10.1590/s1517-83822012000400023
|View full text |Cite
|
Sign up to set email alerts
|

Survival of escherichia coli o157:h7 co-cultured with different levels of pseudomonas fluorescens and lactobacillus plantarum on fresh beef

Abstract: The purpose of this study was to investigate the effect of different levels of Pseudomonas fluorescens (10 2 and 10 6 log 10 cfu/ml) and Lactobacillus plantarum (10 2 and 10 4 log 10 cfu/ml) on the growth of Escherichia coli O157:H7 on beef loins. Beef loins inoculated with E. coli O157:H7 and P. fluorescens were aerobically stored for 7 days at 4 ºC, while those inoculated with E. coli O157:H7 and L. plantarum were vacuum packaged and stored for 8 weeks at 4 ºC. Aerobic Plate Counts (APC), E. coli O157:H7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Besides, in our study, the inhibitory effect of C. maltaromaticum on Enterobacteriaceae did not seem to be influenced by the presence of both inoculated P. fluorescens or B. thermosphacta. Tshabalala, de Kock, and Buys (2012) also report that other LAB species (Lactiplantibacillus plantarum) could impact the growth of Escherichia coli O157:H7 in fresh beef stored aerobically and under vacuum storage, which was not affected by P. fluorescens, regardless of the inoculation level or storage time. Inoculated B. thermosphacta population was also inhibited by Carnobacterium both in ground beef and in cooked ham.…”
Section: Microbiological Countsmentioning
confidence: 86%
“…Besides, in our study, the inhibitory effect of C. maltaromaticum on Enterobacteriaceae did not seem to be influenced by the presence of both inoculated P. fluorescens or B. thermosphacta. Tshabalala, de Kock, and Buys (2012) also report that other LAB species (Lactiplantibacillus plantarum) could impact the growth of Escherichia coli O157:H7 in fresh beef stored aerobically and under vacuum storage, which was not affected by P. fluorescens, regardless of the inoculation level or storage time. Inoculated B. thermosphacta population was also inhibited by Carnobacterium both in ground beef and in cooked ham.…”
Section: Microbiological Countsmentioning
confidence: 86%
“…Experiment in vitro [10] found that lactobacilli inhibited the TLR4 inflammatory signaling induced by enterotoxigenic Escherichia coli via modulation of the inflammation and involvement of TLR2 in human intestinal Caco-2/TC7 cells and intestinal explants. Lactobacillus Plantarum inhibited the growth of Escherichia coli O157:H7 in vitro [11]. Moreover, Lactobacillus Plantarum possesses the ability to improve the growth performance, reducing Enterobacteriaceae , increasing the population of Lactobacillus , the villi height of the small intestine and the concentration of volatile fatty acids in faeces of the broiler [12].…”
Section: Introductionmentioning
confidence: 99%